Translation Strategies Used in BCA’s Company Profile - Jenifer Djobul; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study is done to analyze the translation strategies used in order to translate BCA company profile from Indonesian to English. In doing the study, the writer uses Baker’s (2018) eight translation strategies as the main theory. The methodology of this study is using the descriptive qualitative approach. The result of the study shows that the translator of BCA company profile is using six out of eight Baker’s (2018) translation strategies (translation by a more general word, translation by a more neutral/less expressive word, translation by a cultural substitution, translation by paraphrase using related word, translation by paraphrase using unrelated word, and translation by omission) in order to translate BCA company profile. The loan word and illustration strategies are both not used in the company profile translation. There is also a part which is non-translation.